Faktor-faktor Yang Mempengaruhi Heart Rate Recovery Pada Pasien Yang Menjalani Uji Latih Jantung Dengan Beban - Henry A.P. Pakpahan; Andria Priyana; Adnil Basha; Basuni Radi (The Indonesian Heart Association, 2007)
Background. Heart rate recovery (HRR) has been recognized as an inde-pendent predictor of mortality.Objective.To identify factors that may affect HRR in patient with un-known coronary artery disease (CAD).Methods. This cross sectional study was performed in National Cardiac Center Harapan Kita. We reviewed the chart of patients with unknown CAD who underwent symptom-limited exercise stress testing for medical check up between January – December 2006. Factors that may influence HRR were recorded including current medications, peak exercise heart rate (HR), HR after 3-minute recovery, and the ischemic response to exer-cise. HRR was defined as the change in HR from peak exercise to 3-minute recovery. We further categorized patients to normal or abnormal HRR by using mean HRR as cut off value. All factors related to HRR and normal/abnormal categories were analyzed.Results. There were 188 patients aged 48 + 11 years. HRR significantly influenced by male sex (p=0.003), hypertension (p=0.028), â-blocker (p=0.03), calcium channel blocker (p=0.008), aspirin (p<0.001), and pro-voked ischemia (p=0.005). Using mean HRR (57x) as cut off, patients were classified as having normal (HRR <57x) or abnormal (HRR ? 57x). On fur-ther analysis, there was significant association between age (p=0.003), male sex (p=0.02), hypertension (p=0.02), use of â-blocker (p=0.026) and aspirin (p<0.005).Conclusion. In patients with unknown CAD who underwent symptom-limited exercise stress testing, HRR was influenced by age, male sex, hy-pertension, the presence of provoked ischemia, use of â-blocker, calcium channel blocker, and aspirin.